Oral narrative of individuals with Fetal Alcohol Spectrum Disorder - Ganthous, Giulia [UNESP]; Rossi, Natalia Freitas [UNESP]; Giacheti, Célia Maria [UNESP] (FapUNIFESP (SciELO), 2017)
Purpose: To investigate and compare the oral narrative of individuals with FASD and individuals with typical language development (TLD), as well as to correlate the narrative performance with the score from 4-Digit Diagnostic Code. Methods: Participants were 20 individuals with FASD, of both genders, with chronological age between 6 and 16 years, and 20 individuals with TLD, same gender and similar to the FASD group in age and socioeconomic status. The oral narrative was elicited using the book Frog, where are you? and the data were analyzed in terms of macrostructure, microstructure and global coherence level. Measures regarding the macrostructure included the presence of typical structural elements of storytelling, while the microstructural aspects included words (total and different words), communication units (C-Units), lexical diversity, and mean length of C-Units. Results: Low performance was found in the FASD group for all macrostructural aspects, with the exception of linguistic markers. Among the microstructural aspects, lexical diversity and incomplete C-Units were different between the FASD and TLD groups. The FASD group presented lower global coherence level compared to the TLD group. Negative correlations were found between macrostructural aspects, facial characteristics, and Central Nervous System impairment. Conclusion: Restricted use of typical structural elements of storytelling with lower levels of coherence and reduced vocabulary distinguished the FASD from the TDL group. Future studies may explore whether the association between narrative performance and the 4-Digit Diagnostic Code items present predictive values in the narrative performance of individuals with FASD.
Keywords: Fetal alcohol spectrum disorder; Language; Language and hearing sciences; Language development disorders; Narration; Speech